2018
DOI: 10.1016/j.ccell.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Resistance to Dual Innate Immune and MEK Inhibition Downstream of KRAS

Abstract: Despite extensive efforts, oncogenic KRAS remains resistant to targeted therapy. Combined downstream RAL-TBK1 and MEK inhibition induces only transient lung tumor shrinkage in KRAS-driven genetically engineered mouse models (GEMMs). Using the sensitive KRAS;LKB1 (KL) mutant background, we identify YAP1 upregulation and a therapy-induced secretome as mediators of acquired resistance. This program is reversible, associated with H3K27 promoter acetylation, and suppressed by BET inhibition, resensitizing resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…Similarly, poly(dA:dT) transfection of cancer cells followed by spheroid formation and microfluidic 3-D culture revealed that LKB1-reconstituted 3-D spheroids uniquely responded to transfection of cytoplasmic DNA, significantly upregulating multiple immune cell chemoattractants including CCL5, CCL2, and CXCL10, after 7 days ( Figures 1D,E and Supplementary Figure S1B ). Notably, IL-6 was suppressed by LKB1 reconstitution as previously described ( 24 , 25 ) ( Figure 1E and Supplementary Figure S1B ). In contrast, control MVNs expressed high levels of CCL2 and IL-8, as well as IL-6 ( Supplementary Figures S1C,D ).…”
Section: Resultssupporting
confidence: 75%
“…Similarly, poly(dA:dT) transfection of cancer cells followed by spheroid formation and microfluidic 3-D culture revealed that LKB1-reconstituted 3-D spheroids uniquely responded to transfection of cytoplasmic DNA, significantly upregulating multiple immune cell chemoattractants including CCL5, CCL2, and CXCL10, after 7 days ( Figures 1D,E and Supplementary Figure S1B ). Notably, IL-6 was suppressed by LKB1 reconstitution as previously described ( 24 , 25 ) ( Figure 1E and Supplementary Figure S1B ). In contrast, control MVNs expressed high levels of CCL2 and IL-8, as well as IL-6 ( Supplementary Figures S1C,D ).…”
Section: Resultssupporting
confidence: 75%
“…Since both IRF3 and downstream STAT1 signaling have anti-viral cytotoxic functions, we co-treated cells with Compound 1 (TBK1i) or the JAK/STAT inhibitor Ruxolitinib (Ruxo) to assess the relative contributions of these pathways to STING mediated apoptosis. Whereas TBK1 inhibition itself impaired viability of KL cells (14) yet partially reversed STING cytotoxicity, Ruxo mediated pSTAT1 inhibition strongly rescued STING-induced cell growth arrest and apoptosis (Fig. 4E, F, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In the absence of STING or activation of other viral sensors such as MAVS, TBK1 fails to bridge with IRF3 (16), favoring NF-κB associated induction of alternate cytokines such as IL-6 that instead promote cell survival and myeloid cell recruitment (1,9). Indeed, TBK1 and IKKε mediated pro-tumorigenic cytokine circuits are known to contribute to tumor progression in KRAS mutant lung cancers, involving IL-6-STAT3 activation (9,14). Importantly, epigenetic silencing of DNA sensing was restricted to STING expression, as KL cells maintained cGAS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, addition of the LKB1 mutation to KRAS mutant NSCLC cells is significantly correlated with the aberrant accumulation of cytoplasmic mitochondrial DNA and higher mitochondrial ROS production [113]. Similar to RB-depleted cells that exhibit higher pro-inflammatory cytokines production due to increased mitochondrial ROS, KRAS;LKB1-mutated NSCLC cells highly produce cytokines, such as IL-6 and CCL5 [114,115]. Higher secretion of these pro-inflammatory cytokines not only promotes cell growth and cell survival in a cell-autonomous manner but also contributes to the formation of immunosuppressive TME in a non-cell-autonomous manner [114,115].…”
Section: Role Of Other Tumor Suppressor Proteins In the Tmementioning
confidence: 99%
“…Similar to RB-depleted cells that exhibit higher pro-inflammatory cytokines production due to increased mitochondrial ROS, KRAS;LKB1-mutated NSCLC cells highly produce cytokines, such as IL-6 and CCL5 [114,115]. Higher secretion of these pro-inflammatory cytokines not only promotes cell growth and cell survival in a cell-autonomous manner but also contributes to the formation of immunosuppressive TME in a non-cell-autonomous manner [114,115]. On the other hand, aberrant accumulation of cytoplasmic DNA derived from mitochondria in KRAS;LKB1-mutated NSCLC cells stimulates the cGAS-STING pathway, as discussed above.…”
Section: Role Of Other Tumor Suppressor Proteins In the Tmementioning
confidence: 99%